Managing hypertension in patients with heart failure: an ongoing quandary. (July 2019) - Gupta, Tripti; Rezan, Tameem; Krim, Selim R.
Abstract : Purpose of review: Hypertension (HTN) is one of the strongest risk factors for heart failure and is prevalent in up to 91% of patients with newly diagnosed heart failure. This article offers a practical approach to HTN in patients with heart failure. Recent findings: To date, no randomized trials comparing specific antihypertensive regimens have been conducted in the heart failure population. Management of heart failure with reduced ejection fraction patients with elevated blood pressure (BP) should include guideline-directed medical therapy [angiotensin-converting-enzyme inhibitors (ACEis), aldosterone receptor blockers, AT1 neprilysin-inhibitors, beta blockers and aldosterone blockers] titrated to maximal tolerated doses regardless of BP. Despite the lack of survival benefit current available data suggest the use of ACEis, aldosterone receptor blockers as first-line therapy for HTN in patients with heart failure with preserved ejection fraction. Summary: Management of HTN in heart failure patients should be based on left ventricular function. Recent findings suggest that AT1 neprilysin-inhibitors offer better BP control when compared with ACEi, or aldosterone receptor blockers and therefore should be used as first-line therapy in hypertensive patients with heart failure with reduced ejection fraction. Their role as antihypertensive agents in heart failure with preserved ejection fraction seems promising but remains under investigation.